Serum levels of IL-5, IL-6, IL-8, IL-13 and IL-17A in pre-defined groups of adult patients with moderate and severe bronchial asthma. (July 2019) - Dimitrova, Denitsa; Youroukova, Vania; Ivanova-Todorova, Ekaterina; Tumangelova-Yuzeir, Kalina; Velikova, Tsvetelina
Abstract: Background: Bronchial asthma (BA) is a complex disease characterised by persistent inflammation. Exhaled nitric oxide (FeNO) and blood eosinophil count (b-Eos) are biomarkers for type 2 endotype of BA. Objective: To analyse a panel of serum interleukins and total IgE in predefined by FeNO and b-Eos groups of moderate and severe BA patients. Methods: Serum levels of IL-5, IL-6, IL-8, IL-13 and IL-17A (ELISA) were measured in 30 healthy controls (HC) and 80 adult BA patients. BA patients were split into 4 groups. Group 1:Low FeNO/Low b-Eos (n = 23; 28.8%); Group 2:Low FeNO/High b-Eos (n = 17; 21.3%); Group 3:High FeNO/Low b-Eos (n = 15; 18.8%); Group 4:High FeNO/High b-Eos (n = 25; 31.3%). Results: All interleukins and total IgE were significantly higher in patients with BA as compared with HC. IL-5 levels were highest in Group 2 (p < 0.05). IL-6, IL-13 and IL-17A levels were elevated in Groups 2, 3 and 4 as compared with HC (p < 0.05). Higher IL-8 levels were associated with a pattern of current smokers. Highest IL-17A levels were found in type 2 high groups with frequent exacerbations, mostly uncontrolled and severe BA. We have found a distinct pattern for each group based on demographic, clinical, functional, immunological and inflammatory characteristics. Conclusion: FeNO and b-Eos are useful in the identification of severe type 2 BA subgroups with frequent exacerbations. IL-5, IL-6, IL-13 and IL-17A are involved in the persistent type 2 immune response in moderate and severe BA. We have identified a pattern of refractory, severe type 2/IL-17A high BA in the real clinical practice. Highlights: FeNO and blood eosinophils are useful biomarkers for assessment of bronchial asthma control and severity. The association between high blood eosinophilic count and serum levels of IL-5 was confirmed. There is association of IL-6, IL-13 and IL-17A with type 2 high bronchial asthma. Our approach confirmed the existence of type 2/IL17A high endotype of refractory, severe asthma in the real practice.